Role of IFN‐γ, IL‐13, and IL‐17 on mucociliary differentiation of nasal epithelial cells in chronic rhinosinusitis with nasal polyps. Issue 3 (March 2016) - Jiao, J.; Duan, S.; Meng, N.; Li, Y.; Fan, E.; Zhang, L.
Summary: Background: Mucociliary dysfunction is a prominent pathophysiological feature of chronic rhinosinusitis with nasal polyps (CRSwNP); however, the precise mechanisms underlying mucociliary dysfunction are still unclear. Objective: The aim of this study was therefore to evaluate the effects of IFN‐γ, IL‐13, and IL‐17 on human nasal mucociliary differentiation and ciliary beat frequency (CBF) in patients with CRSwNP. Methods: Human nasal epithelial cells from tissue of patients with CRSwNP and control subjects were established as air–liquid interface (ALI) primary cultures. Confluent cultures were incubated with10 ng/mL each of IFN‐γ, IL‐13, or IL‐17 for 14 days and assessed for expression of specific morphological markers and factors associated with mucociliary differentiation, the percentage of ciliated and goblet cells, and CBF. Results: In comparison with control subjects, percentage of ciliated cells and CBF were decreased; while percentage of goblet cells, FOXJ1, and MUC5AC mRNA expression were increased in nasal polyp‐derived epithelial cultures. Treatment with IFN‐γ and IL‐13 significantly decreased the expression of β‐tubulin IV (specific cilia marker), ciliated cell number, and expression of FOXJ1 and DNAI2, in epithelial cultures derived from both CRSwNP patients and control subjects. Furthermore, while both IFN‐γ and IL‐13 treatment significantly decreased the CBF of cells from both CRSwNP patients and control subjects, IL‐13 additionally significantly increased goblet cell number and the expression of MUC5AC and CLCA1, in these cultures. IL‐17 treatment did not significantly affect ciliated or goblet cell differentiation, CBF, nor MUC5AC and CLCA1 expression, but increased both MUC5B mRNA and protein expression in these cultures. Conclusion and clinical relevance: The demonstration that IFN‐γ and IL‐13 both significantly reduce ciliated cell differentiation and CBF in CRSwNP patients, and IL‐13 additionally induces significant goblet cell hyperplasia and MUC5AC mucin expression, as well as IL‐17 significantly increases MUC5B mucin expression, suggests that these inflammatory cytokines may be potential therapeutic targets in the management of CRSwNP.